STUDY POSSIBLE SUCCESS VISION AND MISSION IN MAKING CITY OF EDUCATION IN THE LONG-TERM DEVELOPMENT PLAN (RPJP) OF METRO CITY PROVINCE OF LAMPUNG 2005-2025 - Fandra Wijaya; Bambang Supriyadi (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
To achieve the success of vision and mission of local government about management planning of development strategy and economic growth require the improvement of professional human resource. The education sector becomes the first mandatory service of local government. This study using David Parmenter theory as a reference, which contain six perspective to assess the success of vision and mission.the six perspective are financial result, customer satisfaction, learning and growth, internal processes, staff satisfaction, community and environment. The research design used was explorative with qualitative approach. Analysis by interview of 16 informants whose related with the research object. The result of the research indicates that the success of realizing as a city of education in normal condition is successful but it is require more policy direction to develop the strategy include: equalization of education staff of each sub-district, the development of professionalism of educators, improvement of basic education service, provision and service of inclusive education, and community empowerment. Recommendations from the author include: the government should plays an active role through stakeholders to implementing a bottom-up system in working with all elements of society. It is hoped that this research can be used as a reference materials or input for local government in preparing the next phase of RPJMD, so that the purpose of vision will in line with the mission of the next five years plans.